Pharmacy mapping using geofencing / Noor Ezwanie Abdul Hamid - Abdul Hamid, Noor Ezwanie (2017)
The cosmetics industry has been growing quickly in both developed and developing countries. These days, Malaysian men also tend to see a personal grooming as a necessity. However, some of cosmetic consumers might face difficulty in searching their desired cosmetic products in pharmacy and to locate the closest pharmacy that sell their preferred cosmetic products. Thus, this project proposed to build a prototype to find the nearest pharmacy that sell that cosmetic products. This can be done by using geofencing technique. The aim of this project is to assist the shoppers to identify which the closest pharmacy that offer their desired cosmetic products. In this project, Rapid Application Development (RAD) methodology is used to develop this prototype because it provides faster development, gives high and maintain the quality of software and reduce development cost. Findings for this system, user enable to find their desired cosmetic products at the nearby pharmacy easily. As the significance of this project, it helped the users to save their time searching for their preferred cosmetic products. In addition, it reduced their travelling time and cost as they know already the location of the pharmacy that sell their preferred cosmetic products. Besides, this project helped to reduce their stress because their cosmetic products are easily accessible at the pharmacy. The recommendation in the future is this project should cover other assortment sort of cosmetic products. Moreover, this project should expect to identify the closest pharmacy that offer different domains such as skincare, personal care and healthcare. Lastly, this application should be develop for any other platform in the future.